2021
DOI: 10.3389/fonc.2021.668481
|View full text |Cite
|
Sign up to set email alerts
|

30-Day Mortality Following Palliative Radiotherapy

Abstract: Purpose30-day mortality (30-DM) is a parameter with widespread use as an indicator of avoidance of harm used in medicine. Our objective is to determine the 30-DM followed by palliative radiation therapy (RT) in our department and to identify potential prognosis factors.Material/MethodsWe conducted a retrospective cohort study including patients treated with palliative RT in our center during 2018 and 2019. Data related to clinical and treatment characteristics were collected.ResultsWe treated 708 patients to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…30-day mortality calculated from start of treatment, 30-day mortality calculated from end of treatment, or treatment in the last 30 days of life. Regardless of this study’s limitations and the unique patient selection, the topic of active treatment in the terminal phase of cancer continues to be important for patients and providers alike [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…30-day mortality calculated from start of treatment, 30-day mortality calculated from end of treatment, or treatment in the last 30 days of life. Regardless of this study’s limitations and the unique patient selection, the topic of active treatment in the terminal phase of cancer continues to be important for patients and providers alike [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not all patients initially thought to represent suitable candidates for radiotherapy are able to complete their treatment. In a recent study by Vázquez et al, 30-day mortality after palliative radiotherapy was 17.5% [ 21 ]. In the multivariate analysis, male gender, ECOG PS 2–3, gastrointestinal and lung cancer were found to be independent factors related to this endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies of patients receiving any palliative RT, rates of 30-DM ranged from 10% to 24%. 4 , 13 , 14 , 15 One recent study of patients with brain metastases from any primary site reported a 30-DM of 28%. 16 We observed a lower rate of 30-DM in our cohort, possibly owing to inclusion of those receiving SRS to limited intracranial metastases, representing a population with a better prognosis.…”
Section: Discussionmentioning
confidence: 99%